2018
DOI: 10.12816/0043811
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Vitamin D Levels in Women with Polycystic Ovarian Syndrome

Abstract: Background: polycystic ovary syndrome (PCOS) is the most common endocrine disorder in women of reproductive age, with a prevalence of 6-10% in the general population. PCOS is characterized by the following: ovulatory dysfunction resulting in oligo-amenorrhea and/or anovulation, hyperandrogenism and/or hirsutism and the presence of polycystic ovarian morphology by ultrasound. Vitamin D also plays a physiologic role in reproduction including ovarian follicular development and luteinization via altering anti-Müll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
(10 reference statements)
1
2
0
Order By: Relevance
“…The results affirm that the vitamin D level was significantly lower in women with PCOS than in those without. This finding is in agreement with those of studies conducted in different countries (8,9,15,18,26,27). It is not consistent with that of a study of women with PCOS living in Makkah, located in the Western region, in which the vitamin D levels were similar among patients and controls (25); nonetheless, a larger study in the same region demonstrated lower levels of vitamin D in women with PCOS (17).…”
Section: Discussionsupporting
confidence: 67%
“…The results affirm that the vitamin D level was significantly lower in women with PCOS than in those without. This finding is in agreement with those of studies conducted in different countries (8,9,15,18,26,27). It is not consistent with that of a study of women with PCOS living in Makkah, located in the Western region, in which the vitamin D levels were similar among patients and controls (25); nonetheless, a larger study in the same region demonstrated lower levels of vitamin D in women with PCOS (17).…”
Section: Discussionsupporting
confidence: 67%
“…According to the study done by the proportion of vitamin D deficiency was higher in women with PCOS than in women without PCOS i.e.59.9%,44% and39.1%. 2,6,14 The mean vitamin D level in women with PCOS was low compared to women without PCOS as seen in the studies done by 11.9±6.9 and 7.7±3.9 6,15 16 The strengths of the present study were a single observer study where cases and controls were matched. The estimation of vitamin D was done in CIDRF using proper calibration.…”
Section: Discussionmentioning
confidence: 63%
“…Elkholy et al, and Kumar et al found a similar trend. 16,17 In contrast in 2018, Gul et al found that PCOS subjects had higher BMI and the difference reached statistical significance (p value <0.01). 15 The observations in this study showed that 76.7% had increased waist-hip ratio (Table 1) with the mean as 0.87±0.08.…”
Section: Table 3: Distribution Of Subjects Based On Acnementioning
confidence: 93%